Oxidative stress response in native algae exposed to the invasive species Batophora occidentalis in S’Estany des Peix, Formentera (Balearic Islands) - Lombardo, Jessica; Tejada, Silvia; Compa, Montserrat; Forteza, Vicent; Gil, Lorenzo; Pinya, Samuel; Sureda, Antoni (Frontiers in Marine Science, 2025)
Algae represent more than 41% of marine biological invasions worldwide. If non-native algae become an invasive and dominant species, they will inevitably affect the characteristics of the ecosystem. The study aimed to evaluate the potential effect of the recently arrived Batophora occidentalis growing over three native algae: Acetabularia acetabulum, Dasycladus vermicularis and Caulerpa prolifera in S’Estany des Peix (Formentera Island, Spain), a shallow saltwater lagoon environment, by means of antioxidant biomarkers. The environmental conditions of the lagoon favoured the extensive progression of B. occidentalis, which since 2020 has progressively been spreading to the entire perimeter of the lagoon where it has found a substrate to attach itself to, even epiphytize native algae. The activities of the antioxidant enzymes (catalase, superoxide dismutase, and glutathione reductase), the phase II detoxification enzyme glutathione S-transferase and levels of malondialdehyde (as an indicator of lipid peroxidation) were evaluated. The results showed significant increases in all monitored biomarkers in the three native algae affected by B. occidentalis, with notable elevations in antioxidant enzyme activities and detoxification response. However, MDA levels increased only in A. acetabulum and D. vermicularis, but not in C. prolifera, suggesting that the latter species exhibits greater resistance to lipid peroxidation. These findings indicate that native algae experience biochemical stress, likely induced by competition or environmental changes caused by B. occidentalis. In conclusion, the presence of the invasive alga B. occidentalis can induce a stressful situation in epiphytized native algae, as evidenced by an increase in oxidative stress biomarkers. Further studies are needed to assess its potential effects on the growth and survival of the affected algae, as well as its ecological impact on the ecosystem.